Case report: Satralizumab therapy for bilateral refractory optic neuritis following the first dose of bivalent human papilloma virus vaccine - Sun, Chuanbin (Frontiers in Immunology, 2024)
Demyelinating optic neuritis (DON) is a rare but sight-threatening ophthalmic condition which occasionally occurs after human papilloma virus (HPV) vaccination. We herein report a case of previously healthy 13-year-old girl who developed a bilateral refractory DON three days after the first dose of bivalent HPV vaccine. The patient experienced bilateral severe visual loss three days after HPV vaccination, and her vision was quickly deteriorated to no light perception one day after the onset of DON. Ophthalmic examination revealed sluggish pupillary light reflex and swollen optic disc in both eyes, and an emergent orbital MRI examination revealed bilateral hyperintensity and enlargement of the intraorbital optic nerve with contrast enhancement. Serological tests for aquaporin-4 IgG antibody, myelin oligodendrocyte glycoprotein IgG antibody, and other common autoantibodies were all negative. The patient showed poor response to 10 days of intravenous methylprednisolone pulse therapy (500 mg, 250 mg, and 125 mg twice per day for 4, 4, and 2 days, respectively). Hence, three-dosed subcutaneous satralizumab was used in the acute stage of DON as an adjunct therapy. Her vision gradually improved after satralizumab therapy, and increased to 20/20 and 20/32 in the right and left eye at the 3-month follow-up. To the best of our knowledge, this is the first case report of satralizumab therapy in the AQP-4 Ab and MOG-Ab dual seronegative isolated DON. Our study indicates that satralizumab may be a safe and efficient adjunct therapy which can be used in the acute stage of the refractory DON poorly responding to steroid pulse therapy.